2013
DOI: 10.1007/s00208-013-0992-4
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-automorphisms of positive entropy on the blowups of products of projective spaces

Abstract: Abstract. We use a concise method to construct pseudo-automorphisms f n of the first dynamical degree d 1 (f n ) > 1 on the blowups of the projective n-space for all n ≥ 2 and more generally on the blowups of products of projective spaces. These f n , for n = 3 have positive entropy, and for n ≥ 4 seem to be the first examples of pseudo-automorphisms with d 1 (f n ) > 1 (and of non-product type) on rational varieties of higher dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The article [22] considers the more general problem of existence of pseudoautomorphisms F X : X X, where π X : X → (P k ) m is a modification of the multiprojective space (P k ) m , obtained as before by blowing up distinct smooth points along an 'elliptic normal curve' C. Our method yields formulas for the pseudoautomorphisms that arise in this case, too. Hence we conclude with a quick sketch of the computations that arise here, laying greatest emphasis on the way things differ from the work presented above.…”
Section: Pseudoautomorphisms On Multiprojective Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The article [22] considers the more general problem of existence of pseudoautomorphisms F X : X X, where π X : X → (P k ) m is a modification of the multiprojective space (P k ) m , obtained as before by blowing up distinct smooth points along an 'elliptic normal curve' C. Our method yields formulas for the pseudoautomorphisms that arise in this case, too. Hence we conclude with a quick sketch of the computations that arise here, laying greatest emphasis on the way things differ from the work presented above.…”
Section: Pseudoautomorphisms On Multiprojective Spacesmentioning
confidence: 99%
“…Following McMullen's approach, Perroni and Zhang [22] recently showed that one can also construct pseudoautomorphisms F X : X X with δ(F X ) > 1 on point blowups X of P k (and more generally, on point blowups of products P k × · · · × P k ). As in McMullen, they begin with a candidate for the pullback action F * X : Pic (P k ) → Pic (P k ), chosen from a certain reflection group.…”
mentioning
confidence: 99%
“…Non-cohomologically hyperbolic maps of 3-dimensional manifolds X arise naturally as certain pseudoautomorphisms that are "reversible" on H 1,1 (X) [6,5,32]. For these mappings it follows from Poincaré duality that λ 1 (ϕ) = λ 2 (ϕ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that (see Lemma 1) if f is a pseudo-automorphism then so are the iterates f n (n ∈ Z). Recent constructions by Bedford-Kim [9], Perroni-Zhang [42], Oguiso [41] [40], and Blanc [4] provided many interesting examples of such maps. Among bimeromorphic selfmaps, it may be argued that the class of pseudo-automorphisms is the second best after that of automorphisms.…”
Section: Introductionmentioning
confidence: 99%